Fatty acid profile and thermal behavior of fat-rich edible insect oils compared to commonly consumed animal and plant oils - Chantakun, Kasidate; Petcharat, Tanyamon; Wattanachant, Saowakon; Ab Karim, Muhammad Shahrim; Kaewthong, Pensiri (Korean Society for Food Science of Animal Resources, 2024)
This study compared the physicochemical properties of edible insect oils from silkworm (Bombyx mori) pupa (SP), sago palm weevil (Rhynchophorus ferrugineus) larva (PW), and bamboo caterpillar (Omphisa fuscidentalis; BC) to oils from chicken skin (CK), beef back fat (BF), pork back fat (PF), salmon belly (SB), sea bass belly (BB), coconut (C), and peanut (P). The fatty acid profiles and thermal behaviors (crystallization and melting) of the extracted oils were evaluated. PW and BC oils had more saturated fatty acids (SFAs) than CK, PF, SB, BB, and P oils. SP oil had equivalent SFA content to CK and BB oils. Insect oils exhibited similar monounsaturated fatty acid concentrations in all samples, except C oils. PW and BC oils exhibited a higher content of palmitoleic acid than the other oils. SP oils contained polyunsaturated fatty acids similar to those in SB and BB oils, which were higher than those in PW, BC, CK, BF, and PF oils. SP oil also exhibited the highest concentration of α-linolenic acid (C18:3 n-3). Arachidonic acid (0.01–0.02 g/100 g) in all insect oils was lower level compared to CK, BF, PF, SB, and BB oils. SP oil (0.03 g/100 g) exhibited a slightly higher level of eicosapentaenoic acid compared to PW (0.01 g/100 g) and BC (0.01 g/100 g) oils. The insect oils were liquid at ambient temperature, solid below –15℃, and required less energy (∆Hm-max) for melting than other samples. This study indicated that insects, particularly SP, could serve as an alternative source of fat to meet its growing demand.